FIRST RECORD OF DIOPATRA CLAPAREDII GRUBE, 1878 (ONUPHIDAE, POLYCHAETA) FROM INDONESIAN WATERS, WITH SOME NOTES ON ITS ECONOMIC IMPORTANCE - Joko Pamungkas; Atang Atang; Eko S. Wibowo (Treubia, 2023)
Diopatra claparedii Grube, 1878, is a common polychaete species that occurs in Southeast Asian countries, including Malaysia, Singapore, Thailand, and the Philippines. However, the occurrence of this species in Indonesia has never been recorded. In the present study, we identified the presence of D. claparedii in the eastern part of the Segara Anakan Lagoon in Cilacap, Central Java Province. Thespecies is characterized as having distinct pectinate chaetae with funnel-like combs. The worms, like in some other Asian countries, are commercially exploited for use as fishing bait. The distributional map of this species is provided in this article.